1985
DOI: 10.1111/j.1365-2672.1985.tb03330.x
|View full text |Cite
|
Sign up to set email alerts
|

A note on the use of metal species in microbiological tests involving growth media

Abstract: The feasibility of using traditional growth media for biological testing of metal species, for example as potential microbiocides, was investigated. Significant interactions between both of the representative metal species studied, Cu2+ and FeEDTA, and the test media were found. It is recommended that the use of growth media for tests on metal species should be avoided.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

1987
1987
2011
2011

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(9 citation statements)
references
References 5 publications
0
9
0
Order By: Relevance
“…This explains why Tetrahymena pyrifbrmis can tolerate a 1 00-fold higher concentration of Cu(I1) in a rich organic medium than in a defined one (Nilsson, 1981), why addition of yeast extract to cultures of Aerobacter aerogenes (Klebsiella pneumoniae) protects the bacteria from the usual toxic effects of Cu(I1) (MacLeod et al, 1967), and why yeast extract can alleviate the toxic effects of Ag(1) on the oxidation of Fe( 11) by Thiobacillus jerrooxidans (Tuovinen et al, 1985). Bird et al (1985) have also drawn attention to the effect of growth medium on the chemical speciation of Cu(II), and the implication for toxicity studies.…”
Section: Complexa T Ionmentioning
confidence: 99%
“…This explains why Tetrahymena pyrifbrmis can tolerate a 1 00-fold higher concentration of Cu(I1) in a rich organic medium than in a defined one (Nilsson, 1981), why addition of yeast extract to cultures of Aerobacter aerogenes (Klebsiella pneumoniae) protects the bacteria from the usual toxic effects of Cu(I1) (MacLeod et al, 1967), and why yeast extract can alleviate the toxic effects of Ag(1) on the oxidation of Fe( 11) by Thiobacillus jerrooxidans (Tuovinen et al, 1985). Bird et al (1985) have also drawn attention to the effect of growth medium on the chemical speciation of Cu(II), and the implication for toxicity studies.…”
Section: Complexa T Ionmentioning
confidence: 99%
“…These transfer properties represent a natural way of dispersing new adaptivc genetic abilities in bacterial populations inhabiting heavy-metal pol- Unknown [27] luted environments [62]. The use of culture mcdia with different abilities to complex cupric ions [63,64] has resulted in reported MIC copper values ranging from 1 to 20 mM for plasmid-containing resistant strains, depending on the testing conditions. Plasmid-determined resistance to copper has been found in diverse Gram-negative bacterial species ([15]: Tablc 2), but only threc copper resistance determinants have been analyzed to the molecular level [20,22,24,28-30].…”
Section: Plasrnid-mediated Copper Resistancementioning
confidence: 99%
“…Media containing only inorganic salts are close to ideal from the chemical point of view, as long as the test organism can tolerate or survive in such conditions (Twiss et al, 2000). However, Bird et al (1985), Hughes and Poole (1991), reported that the composition of the growth medium can have a significant effect on the reactivity and bioavailability of a metal. Consequently, a given metal may exhibit vastly different toxicities when cells are grown in media with different composition.…”
Section: Introductionmentioning
confidence: 99%